(untitled) (Journal of the Management Sciences, 2024)
Digital transformation which is imperative for all businesses, from the small to the big enterprise, is the process of using digital technologies to create new or modify existing business processes, culture, and customer experiences to meet changing business and market requirements. The purpose of this paper is to investigate how digital transformation affects marketing activities in small and medium-sized enterprises (SMEs) in Owerri, Imo State. The primary research question focuses on the current evolution of marketing activities performed by organizations. A descriptive research design was used. The conceptual frame work was developed to identify the variables, dimensions and indicators to prepare effective questionnaire. The primary data are collected through questionnaire which consists of 34 questions to each relevant area. The questionnaire was distributed among 50. The study employed regression technique and based on the hypothesis tested, it was clear that there is strong positive relationship between all independent variables (Compatibility, Cost Effectiveness, Trust and Interactivity) and dependent variable (Business Performance) in the conceptual framework. Hypothesis of all null hypotheses are rejected and alternative hypothesis of all variables have to be accepted. It can be proved on significant test of analysis with evaluating Sig. value less than alpha (0.05) level (0.000< 0.05). It means all independent variables have an impact to the dependent variable. The findings shown that digital technologies are widely used in marketing in the enterprises studied, despite the fact that these technologies are often classified as traditional tools. IT technologies and digital tools also have an impact on marketing, assisting in the development of customer relationships and increasing the value of each organization.